Dynamic Methylome Modification is Associated with Mutational Signatures in Aging and the Etiology of Disease - Krishnasamy, Kashyap; Pasha, Naseer; Kumar, Gayatri; Nagarajan, Naveenkumar; Mam, Bhavika; Kishinani, Mahima; Vohra, Vedanth; Jain, Renuka; Patell, Villoo Morawala (Archives of Clinical and Medical Case Reports, 2022)
Reversible epigenetic changes within the loci of genes that regulate critical cell processes have recently emerged as important biomarkers of disease pathology. It is then natural to consider the consequences for population health risk of such epigenetic changes during the aging process. Specifically, the interplay between dynamic methylation changes that accompany aging and mutations that accrue in an individual’s genome over time needs further investigation. The current study investigated the role of dynamic methylation acting together with gene variants in an individual over time to gain insight into the evolving epigenome–genome interplay that affects biochemical pathways controlling physiological processes during aging. We completed whole-genome methylation and variant analysis in a non-smoking Zoroastrian-Parsi individual, collecting two samples, 12 years apart (at 53 and 65 years respectively) (ZPMetG-Hv2a-1A (old, t0), ZPMetG-Hv2a-1B (recent, t0+12)) and analyzing them using a GridION Nanopore sequencer at 13X genome coverage overall. We further identified the single nucleotide variants (SNVs) and indels in known CpG islands by employing the Genome Analysis Tool Kit (GATK) and MuTect2 variant-caller pipeline with the GRCh37 (patch 13) human genome as a reference. We found 5258 disease-relevant genes that had been differentially methylated in this individual over 12 years. Employing the GATK pipeline, we found 24,948 genes, corresponding to 4,58,148 variants, specific to ZPMetG-Hv2a-1B, indicating the presence of variants that had accrued over time. A fraction of the gene variants (242/24948) occurred within the CpG regions that were differentially methylated, with 67/247 exactly coincident with a CpG site. Our analysis yielded a critical cluster of 10 genes that were each significantly methylated and had variants at the CpG site or the ±4 bp CpG region window. Kyoto Encyclopaedia of Genes and Genomes (KEGG) en